Contribution of the use of nanomaterials in cement matrix through additive manufacturing aiming at sustainable construction - Corso, Marla; Leles da Silva, Maicon Douglas; Reitz Cardoso, Flavia Aparecida Reitz Cardoso; Soto Herek Rezende , Luciana Cristina; Marques Sastre , Rodolfo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Reducing the environmental impact and complying with the social commitments, as well as respecting the environment to promote sustainability in production processes has been debated in various sectors and, in construction processes, technology is an ally, as automation and the insertion of components into materials, there is a decrease in waste and an improvement in the quality of buildings. Therefore, this study aimed to evaluate the constructability and extrudability in civil construction by inserting graphite and graphene oxide in a cementitious matrix. The cementitious filaments produced were evaluated for physical, Chemical, and mechanical parameters. The results indicated that the insertion of both graphite and graphite oxide in the cementitious matrix did not interfere with the extrudability and constructability of the material. Values of 9.34 MPa, 8.99 MPa, and 8.91 MPa were obtained for flexural tension in the samples added with 0.04% and 0.1% of graphite and 0.04% of graphene oxide, respectively. When evaluated for axial compression, the samples containing 0.1% and 0.2% graphene oxide and the reference sample had 127,546.00 MPa, 127,350.05 MPa, and 126,844.12 MPa, respectively. The sample with 0.1% graphite showed a positive behavior in relation to the tensile test in flexion, compression, and less deformation after printing, making it feasible to add nanomaterials in cementitious filaments for additive manufacturing to produce more resistant materials.